Pengaruh Coffee Shop Atmosphere, Service Experience, dan Brand Personality terhadap Customer Satisfaction Tomoro Coffee di Kota Surabaya - Dea Riska Ananta Djawak; M. Sihab Ridwan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the influence of Coffee Shop Atmosphere, Service Experience, and Brand Personality on Customer Satisfaction at Tomoro Coffee in Surabaya. The research employs a quantitative method involving 100 respondents selected using purposive sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using IBM SPSS version 26, including validity, reliability, classical assumption tests, multiple linear regression, t-test, and F-test. The results indicate that all three variables have a positive and significant effect on customer satisfaction, both partially and simultaneously. Brand Personality is the most dominant variable influencing satisfaction. The coefficient of determination (R²) value of 0.750 explains that 75% of customer satisfaction variation is affected by these variables. The findings highlight that a pleasant coffee shop atmosphere, excellent service quality, and a strong brand personality are essential in enhancing customer satisfaction at Tomoro Coffee Surabaya.